Membaca Kembali Realitas Sosial melalui Karl Marx: Refleksi Kritis atas Pendidikan dan Pengabdian Keagamaan - Fadlullah, Ahmad; Mulyani, Mulyani (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2025)
This article aims to analyze academic and religious life through the lens of Karl Marx’s thought, particularly the concepts of historical materialism, alienation, and ideology. Using a qualitative reflective-hermeneutic approach, the author reflects on personal experiences as a postgraduate student, Islamic boarding school administrator, and teacher at a Qur’anic Education Center (TPQ). Historical materialism is employed to examine how economic structures influence life choices, work routines, and educational orientations. Meanwhile, alienation is identified in the disconnection between idealized spiritual values and the technical, repetitive nature of daily work. Ideology is analyzed as a symbolic mechanism that normalizes social inequalities in the form of academic meritocracy and the romanticization of religious service. The findings reveal that critical awareness of social and ideological structures is key to understanding both limitations and the potential for transformation in everyday life. This article further emphasizes the importance of praxis in the form of reflective-transformative action as a synthesis of consciousness and social change. Such an approach is highly relevant in the context of Islamic education, aligning with the value of muhasabah as an evaluative effort toward a more conscious and liberating orientation of life and action.